(untitled) (Medico Legal Update, 2020)
The muscular training by adopting fixed foundations is a modern training methods which is concerned with the development of muscle strength, in fullest stretch This is due to the quality of the exercises that selected and designed according to the requirements of skill performance which performance is subject to a set of variables that determine the characteristics of this technical performance of the hit/spike skill, it causes production of the kinetic system, needed by good skill performance as well as the appropriate correct compatibility that occurs between the variability in the kinematic and kinetic variables determined by the stress used is the best way to success performance as well as the stabilization and orientation of muscle groups to serve skill performance, so the researchers used the experimental method using experimental design of one group appropriate to the nature of the research, the The study sample was chosen by the researchers in purposive method, numbering 6 athletes, The researchers were keen to apply the stationary strength training using different tools for the purpose of some Bio kinematics indicators and the development of muscle strength for sample members (8) weeks and included (24) training units (3) units per week, The results of the research was the most important that all the exercises used to develop the fixed force, whether the muscles of the legs, torso or arms, increased the efficiency of the internal force, the strength of ligaments in the production of torque force.